2021
DOI: 10.3389/fpsyt.2021.669783
|View full text |Cite
|
Sign up to set email alerts
|

Structural Differences Between Healthy Subjects and Patients With Schizophrenia or Schizoaffective Disorder: A Graph and Control Theoretical Perspective

Abstract: The coordinated dynamic interactions of large-scale brain circuits and networks have been associated with cognitive functions and behavior. Recent advances in network neuroscience have suggested that the anatomical organization of such networks puts fundamental constraints on the dynamical landscape of brain activity, i.e., the different states, or patterns of regional activation, and transition between states the brain can display. Specifically, it has been shown that densely connected, central regions contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…This sample has previously been used by our group to explore structural deficits in patients with ScZ [Dimulescu et al. ( 25 )]. From the sample of 43 patients and 43 healthy control participants, we excluded 5 patients due to missing resting-state functional MRI (rs-fMRI) data or artefacts/excessive motion identified during the pre-processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sample has previously been used by our group to explore structural deficits in patients with ScZ [Dimulescu et al. ( 25 )]. From the sample of 43 patients and 43 healthy control participants, we excluded 5 patients due to missing resting-state functional MRI (rs-fMRI) data or artefacts/excessive motion identified during the pre-processing.…”
Section: Methodsmentioning
confidence: 99%
“…Computational models of large-scale brain circuits can be used to investigate dynamical circuit mechanisms linking local ScZassociated alterations to global changes in the functional organisation of the brain. Leveraging such computational models, studies have shown that decreases in global inter-regional connectivity strengths can lead to wide-spread functional disruptions [Cabral et al (21)], increased global signal variance [Yang et al (22)] and altered topological characteristics of functional brain networks (Cabral et al (23,24) resembling ScZ. However, except for Yang et al (22), these studies only investigated a global scaling of the inter-regional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The study sample was collected through the Center for Biomedical Research Excellence (COBRE) led by Dr. Vince Calhoun (more information here: http://fcon1000.projects.nitrc.org/indi/retro/cobre.html ) and obtained from the SchizConnect database ( http://schizconnect.org ). This sample has previously been used by our group to explore structural deficits in patients with ScZ (Dimulescu et al (2021)). From the sample of 43 patients and 43 healthy control participants, we excluded 5 patients due to missing resting-state functional MRI (rs-fMRI) data or artefacts/excessive motion identified during the pre-processing.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the emerged states in brain dynamics, we focus on synchronized patterns on brain systems, where regions are divided into different functional regions with similar cognitive processes. For this network, each region is assigned to one of eight cognitive systems ( Yeo et al, 2011 ), including somatomotor (Som), default mode network (DMF), control (Con), dorsal attention (DA), limbic (Lim), visual (Vis), ventral attention (VA), other (Oth, subcortical regions could not be assigned to any system) ( Dimulescu et al, 2021 ). Figure 7 exhibits the assignment of 94 AAL2 brain regions within eight cognitive systems.…”
Section: Chimera States On Brain Networkmentioning
confidence: 99%
“…To investigate how chimera states in brain are influenced by stimulation of various brain regions, we integrate WCOs on brain networks and stimulate single region with three global coupling strengths. Results show the existing of three different states, i.e., the coherent, chimera, and metastable state (Yeo et al, 2011;Dimulescu et al, 2021), and suggest that the Kuramoto order parameter is weakly and negatively correlated with the chimera index. Besides, higher degree nodes have a more centralized and compact distribution of the ranked order parameter compared to lower ones.…”
Section: Introductionmentioning
confidence: 97%